PEMANFAATAN DATA SATELIT ADEOS UNTUK PEMANTAUAN KESUBURAN PERAIRAN DAN IDENTIFIKASI DAERAH PENANGKAPAN IKAN - Sachoemar, Suhendar I (Jurnal Sains dan Teknologi Indonesia, 2006)
Sea Surface Temperature (SST) and Chlorophyll-a (SSC) can be detected by Ocean Color and Thermal Scanner (OCTS) derived from the Advance Earth Observation Satellite (ADEOS) sensor. These parameters are useful to estimate the potential fishing ground by identification of the upwelling and marine productivity on the study of fisheries oceanography within the tropical area of Indonesia.